Law Enforcement Arrangements in Online Prostitution in Indonesian Security Context - Firdausa, Lina Rosyidah (Faculty of Law Universitas Negeri Semarang, 2022)
This research is descriptive normative legal research with a statutory approach, which examines laws and regulations related to the legal issues raised and an analytical approach. the text of a statute. The type of data used is secondary data. The secondary data sources used include primary legal materials, secondary legal materials, and tertiary legal materials. The data collection technique used is the study of documents or library materials. The study of documents or library materials includes efforts to collect data by visiting libraries, reading, reviewing, and studying books, literature, articles, magazines, newspapers, scientific essays, papers, internet related to the object of research. The results of the study show that Indonesia's positive legal regulations regulate crime of pornography on the internet (cyberporn) as a cybercrime including Article 281-283 of the Criminal Code (KUHP), Law Number 8 of 1992 concerning Film, Law Number 36 of 1999 concerning Telecommunication, Article 5 paragraph 1 and Article 13 paragraph (1) letter a of Law Number 40 of 1999 concerning the Press, Article 36 paragraph (5) of Law Number 32 of 2002 concerning Broadcasting, Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE Law) and Law Number 44 of 2008 concerning Pornography. The regulation is considered inadequate when it comes to the current development of pornography on the internet (cyberporn), including the provision of unclear limits on pornography, the authorities to take certain actions in dealing with the problem of pornography, the threat of punishment that is too light, the lack of clarity on the parties deemed appropriate for the crime. accountable for crimes categorized as pornography, and inconsistent law enforcement.